2013
DOI: 10.36095/banxico/di.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Bank Competition and Account Penetration: Evidence from Mexico

Abstract: This paper documents a positive relation between bank competition and the penetration of bank accounts at the municipal level in Mexico. To account for potential biases in our regressions due to the endogeneity of market structure, we employ a two-stage estimation approach based on an equilibrium structural model. Our preferred estimate implies that moving from a monopoly to a duopoly will lead to an increase of 1,016 accounts per 10,000 adults, a 42 % increase over the cross-municipality mean. This is compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In this regard, the study made by Anderson, Baker & Robinson (2017) shows that saving behavior is mostly driven by perceived, not actual, financial literacy of individuals and therefore people have mistaken beliefs about financial products. Financial literacy and financial inclusion can be increased by the competitiveness of financial institutions, which will develop more accessible financial products for their clients (Marin & Schwabe, 2019). Several authors had studied the link between financial literacy and people behavior, concluding that highly financial literacy is related with a decreased indebtedness (Gerardi, Goette & Meier, 2013), savings and investments in the stock market (Almenberg & Dreber, 2015), capacity to handle unexpected expenses (Hasler, Lusardi & Oggero, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, the study made by Anderson, Baker & Robinson (2017) shows that saving behavior is mostly driven by perceived, not actual, financial literacy of individuals and therefore people have mistaken beliefs about financial products. Financial literacy and financial inclusion can be increased by the competitiveness of financial institutions, which will develop more accessible financial products for their clients (Marin & Schwabe, 2019). Several authors had studied the link between financial literacy and people behavior, concluding that highly financial literacy is related with a decreased indebtedness (Gerardi, Goette & Meier, 2013), savings and investments in the stock market (Almenberg & Dreber, 2015), capacity to handle unexpected expenses (Hasler, Lusardi & Oggero, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it is possible to have a positive relationship between concentration and financial development as documented by Marín and Schwabe (2013). They used Mexico with the employment of two-stage estimation.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Their results suggested that concentration in the banking industry is positively associated with financial development in lower middle- and low-income countries. Marín and Schwabe (2012) documented a positive relation between local bank competition, proxied by concentration and the number of banks, and the penetration of deposit accounts and credit cards in Mexico. Love and Martínez Pería (2012) showed that competition had a positive relationship with the firm’s access to finance in a panel of 53 countries coupled with the use of Lerner index to measure competition.…”
Section: Brief Literature Reviewmentioning
confidence: 99%